Factors associated with bronchiectasis in patients with moderate–severe chronic obstructive pulmonary disease. Issue 29 (July 2016) - Jin, Jianmin; Yu, Wenling; Li, Shuling; Lu, Lijin; Liu, Xiaofang; Sun, Yongchang
Abstract : Abstract: A high prevalence of bronchiectasis was found by chest computed tomography (CT) in patients with moderate–severe chronic obstructive pulmonary disease (COPD), and it was shown to be associated with more severe symptoms, higher frequency of exacerbations and mortality. The risk factors for bronchiectasis in COPD are not yet clarified. High-resolution computed tomography (HRCT) of chest was performed in patients with moderate–severe COPD, and the presence and the extent of bronchiectasis were evaluated by two radiologists. Demographic data, respiratory symptoms, lung function, previous pulmonary tuberculosis, serum inflammatory markers, serum total immunoglobulin E (T-IgE), and sputum culture of Pseudomonas aeruginosa were compared between those with and without bronchiectasis. Multivariate logistic regression analysis was used to determine the independent factors associated with bronchiectasis. We enrolled 190 patients with stable COPD, of which 87 (87/190, 45.8%) had bronchiectasis on HRCT. Compared with those without bronchiectasis, COPD patients with bronchiectasis were more likely to be males ( P = 0.021), had a lower body mass index (BMI) ( P = 0.019), a higher prevalence of previous tuberculosis ( P = 0.005), longer history of dyspnea ( P < 0.001), more severe dyspnea ( P = 0.041), higher frequency of acute exacerbation ( P = 0.002), higher serum concentrations of C-reactive protein (CRP) ( P = 0.017), fibrinogen ( P = 0.016), and T-IgE [ P = 0.004; for log10 (T-IgE), P <0.001]. COPD patients with bronchiectasis also showed poorer lung function (for FEV1 /FVC, P = 0.013; for FEV1 %predicted, P = 0.012; for global initiative for chronic obstructive lung disease (GOLD) grades, P = 0.035), and a higher positive rate of sputum P aeruginosa ( P = 0.020). Logistic regression analysis demonstrated that male gender ( P = 0.021), previous tuberculosis ( P = 0.021), and increased level of serum T-IgE [for log10 (T-IgE), P < 0.001] were risk factors for coexistent bronchiectasis. More notably, the level of serum T-IgE [log10 (T-IgE)] was positively correlated with the extent of bronchiectasis in COPD patients ( r = 0.208, P = 0.05). Higher serum T-IgE, male gender, and previous tuberculosis are independent risk factors for coexistent bronchiectasis in COPD. The association of T-IgE with the extent of bronchiectasis also suggests that further investigations are needed to explore the potential role of IgE in the pathogenesis of bronchiectasis in COPD.